MULTILINGUAL EDUCATION – A STEP INTO THE BETTER FUTURE - Tvaltvadze, Darejan; Mumladze, Eteri; Gvelesiani, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Contemporary globalizing processes are often associated with plurilingualism, translanguaging and multiliteracies that foster the implementation of multilingual education in the countries facing an increasing diversity: the mass migration of population, the growing number of refugees, settlements of ethnic minorities. The paper deals with the presentation of the latest state policies directed towards the implementation of multilingual education in Georgia – in the post-Soviet country, which has undergone drastic changes during the last decades. In the Soviet epoch, mastering Georgian or Russian was a prerequisite of a rightful citizenship. After the dissolution of the USSR, mastering Georgian started being obligatory for occupying positions in governmental institutions, organizations, etc. This fact marginalized those representatives of ethnic minorities, who had a poor knowledge of the state language. The government initiated the implementation of multilingual educational policies preventing marginalization of ethnic minorities and facilitating the rearing of plurilingual citizens sharing equal rights and responsibilities. The paper presents certain insights into the multilingual education and makes specific proposals regarding the:usage of innovative teaching methods, models and approaches (CLIL approach, heteroglossic approach);creation of an appropriate lesson design;implementation of intensive training-courses focused on the acquisition of intercultural and cross-national skills, etc.The methodology of research includes observation, analysis and evaluation of ongoing processes.